2004
DOI: 10.1001/archotol.130.11.1313
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Snoring of Structural Nasal Valve Dilatation With a Butterfly Graft

Abstract: To evaluate the effect on snoring of structural nasal valve dilatation with butterfly spreader grafts in patients with nasal valve insufficiency. Design: Retrospective medical chart review and telephone follow-up; mean ± SD follow-up time, 20.7±11.34 months (range, 3-48 months). Settings: Tertiary care referral center. Subjects: A total of 37 snoring patients with nasal valve insufficiency who underwent nasal valve dilatation with a butterfly spreader graft. Interventions: The conchal cartilage butterfly graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 21 publications
2
42
0
1
Order By: Relevance
“…Loth et al [32] showed that the use of nasal dilators significantly improved snoring complaints. Akcam et al [33] performed nasal valve surgery in 37 patients and found a 65% decrease in snoring in a retrospective evaluation. In our study, there was a significant improvement in snoring complaints of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Loth et al [32] showed that the use of nasal dilators significantly improved snoring complaints. Akcam et al [33] performed nasal valve surgery in 37 patients and found a 65% decrease in snoring in a retrospective evaluation. In our study, there was a significant improvement in snoring complaints of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms such as nasal obstruction and congestion may have different outcomes ranging from chronic mouth breathing to the need for endonasal surgery. When history and physical examination lead to an anatomical diagnosis of weakness of the nasal side wall, strengthening the side wall with grafts is a direct solution to the problem, as confirmed by previously published studies [10,11].…”
Section: Discussionmentioning
confidence: 59%
“…Over the past 10-15 years, there has been an increased awareness of the nasal valve as a contributor to nasal airway obstruction, resulting in a fl urry of scientifi c publications on the matter, innovations in therapeutic options, and increasing applications of a multitude of both surgical and nonsurgical treatments to correct the nasal valve contribution to nasal obstruction (Park 1998 ;Kern 1978 ;Gassner et al 2006 ;Friedman et al 2004 ;Paniello 1996 ;Akcam et al 2004 ;Vaiman et al 2005 ;Guyuron et al 1998 ;Toriumi et al 1997 ;Sen and Iscen 2007 ;Mendelsohn and Golchin 2006 ;Ng et al 1998 ;Sheen 1984 ;Clark and Cook 2002 ;Stucker et al 2002 ;Stucker and Hoasjoe 1994 ;Menger 2006 ;Rohrich et al 2002 ;Andre et al 2006 ;Byrd et al 2007 ). Evaluation of the patient begins with a thorough history, eliciting signs that may hint at nasal obstruction and nasal valve collapse.…”
Section: Treatmentmentioning
confidence: 99%